Trombosis venosa cerebral: una etiología rara - Nuno Leal; António Campos; Miguel Veloso; José Ribeiro Almeida; Pedro Barros; Sara Pinto (Sociedade Galega de Medicina Interna, 2023)
Idiopathic thrombocytopenic purpura is an immune-mediated disease that courses with thrombocytopenia. Eltrombopag is a thrombopoietin receptor agonist used as a second-line treatment for this disease to increase platelet count. The association of this drug with thrombotic events is known, however, with few cases of venous sinus thrombosis described in the literature. We present a 26-year-old female with idiopathic thrombocytopenic purpura diagnosed at the of age 14, splenectomized and previously treated with immunoglobulins, corticosteroids, and rituximab, with no response, who was started on oral estroprogestative and eltrombopag, with multiple dose increases, for 3 months. She was admitted to the emergency room with a 3-day history of severe frontal headache, with phono and photophobia, nausea, vomiting, and confusion. Physical examination was remarkable only for mild paraphasias, anomalous pauses, and difficulty in reading. Routine labs showed mild thrombocytopenia, leukocytosis, and elevated C-reactive Protein. She performed a brain computerized tomography and magnetic resonance that demonstrated extensive venous sinus thrombosis. She was admitted to the ward with eltrombopag suspension and enoxaparin 1mg/kg bid. Increasing thrombocytosis was observed for nine days, with a subsequent decrease to normal levels. Sequenced cerebral tomography showed hemorrhage reabsorption. At discharge, there was no improvement of neurological deficits and dabigatran 150mg bid was started for secondary prophylaxis. Despite contradictory data relating specifically to eltrombopag, a thrombotic event following multiple dose increases was described before, and it makes the more likely culprit for this event. The treatment of venous sinus thrombosis is based on anticoagulants, and we chose dabigatran for the ease of use and the existence of a readily available antidote. This association between eltrombopag and thrombosis means patients should be advised to avoid prothrombotic risk factors such as smoking, obesity, oral estroprogestative, and immobilization. Some common symptoms associated with this drug, like headache and nausea should always be taken seriously, since they can be also found in venous sinus thrombosis.